Rotational relaxation characteristics of the monoclinic phase of CCl4 - Zuriaga, Mariano Jose (2011)
We present a study of crystalline CCl4 spanning up to 10 orders of magnitude in time at temperaturesranging from 160 K to 190 K using molecular dynamics simulations. The relaxation processis studied using angular self correlation functions. The results show that each of the four nonequivalentmolecules of the monoclinic phase have a particular relaxation time. Two of the moleculesrelax in an exponential way and the two other molecules have a more complex behavior, especiallyat the lower temperatures. In all cases, the molecular rotations correspond to quick jumps betweenequivalent tetrahedral equilibrium positions.Most of these rotations are about the C3 symmetry axes,however at high temperatures, rotations about the C2 symmetry axes are observed as well. The waitingtime between rotations follows a Poisson distribution. The calculated relaxation times show anArrhenius behavior with different activation energy for different nonequivalent molecules, in linewith recently published findings of nuclear quadrupole resonance experiments.